1995
DOI: 10.1093/bja/75.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Volume preloading is not essential to prevent spinal-induced hypotension at caesarean section

Abstract: We have compared the protective effect of 1000 ml preload with 200 ml preload of crystalloid solution, administered during the 10 min before spinal anaesthesia was induced, in 60 healthy women with no fetal compromise undergoing elective Caesarean section. The spinal anaesthetic was managed identically in both groups by an anaesthetist who was unaware of the volume of fluid administered. A prophylactic infusion of ephedrine 60 mg in Hartmann's solution 500 ml was given according to maternal arterial pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(97 citation statements)
references
References 15 publications
3
80
1
8
Order By: Relevance
“…Fluid prehydration may result in increases in central venous pressure, pulmonary oedema and haemodilution which reduce fetal oxygenation if hypotension also occurs. 11,12 There is an additional risk of circulatory overload which can occur with contraction of the uterus after delivery or when the block regresses. 12,13 We demonstrated a higher incidence of hypotension in the prehydration group, 70% compared with 40% in the ephedrine group (P = 0.037).…”
Section: Discussionmentioning
confidence: 99%
“…Fluid prehydration may result in increases in central venous pressure, pulmonary oedema and haemodilution which reduce fetal oxygenation if hypotension also occurs. 11,12 There is an additional risk of circulatory overload which can occur with contraction of the uterus after delivery or when the block regresses. 12,13 We demonstrated a higher incidence of hypotension in the prehydration group, 70% compared with 40% in the ephedrine group (P = 0.037).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of preload in the prevention of hypotension has been questioned. Two studies, by Jackson et al [62] and Rout et al [63], have found little value in crystalloid preloads. Neither study showed a clinical difference between groups receiving and not receiving a fluid bolus, in terms of hypotension, severity of hypotension, Apgar scores, or cord gases.…”
Section: Prevention Of Hypotension Using Crystalloid Preloadmentioning
confidence: 99%
“…The use of vasopressors is required. 4 The optimal vasopressor should offset the progressive effects of ascending sympathetic blockade, which is difficult to achieve because the ␣-and ␤-adrenergic activities can vary independently during blockade installation. Still, changes in sympathetic activity may be organ-specific (inhibition of cardiac fibers), region-specific (inhibition in the lower body and increased activity in the upper body) or systemic (inhibition of catecholamine release from the adrenal medulla).…”
Section: Introductionmentioning
confidence: 99%